Teachers and pre-service teachers as partners in collaborative teacher research: A systematic literature review - Willegems, Vicky; Consuegra, Els; Struyven, Katrien; Engels, Nadine (Teaching and Teacher Education, 2017)
A systematic literature review (N = 14) was performed with a focus on the influence of collaborative teacher research on the professional development of pre-service teachers (PTs). A thematic overview of reported outcomes is presented. Collaborative teacher research has proven itself to be a promising practice for improving PTs' knowledge and attitudes regarding collaboration, reflection, inquiry, and student-centred teaching. Shared inquiry in less hierarchical partnerships between pre-service and in-service teachers, and other multiple actors, advances PT's learning more than one-to-one relationships between a mentor and a PT.
Keywords: Collaborative teacher research; Pre-service teacher; Pre-service teacher education; Professional development; Teacher collaboration